Exploring the drivers of green supply chain management in the Chinese electronics industry: Evidence from a GDEMATEL–AISM approach - Yi Li; Yongqi Tan; Yang Pu; Yunying Zhu; Haotian Xie (Cleaner Logistics and Supply Chain)
The electronics industry plays a crucial role in our information-based and intelligent society, but it also contributes significantly to environmental pollution. This study aims to explore the factors that drive green supply chain management (GSCM) in this industry using a mixed-method approach. Initially, we conduct a comprehensive literature review and interview three experts to identify ten key variables influencing GSCM. Subsequently, we propose a novel method called Gray Decision-Making Trial and Evaluation Laboratory–Adversarial Interpretive Structure Modeling (GDEMATEL–AISM) to analyze the interactions, relationships, and hierarchical structure of these driving factors, visually representing them. To ensure the robustness of our findings, we perform sensitivity analysis by considering different scenarios with expert weights. For model evaluation, we utilize a case study within China’s electronics industry. Our research reveals that green innovation exerts the most significant influence on GSCM practices. Additionally, green marketing, green manufacturing, and production needs emerge as crucial short-term priorities. To promote the sustainable development of GSCM, we propose corresponding strategic measures that focus on these key drivers. These insights provide valuable guidance for practitioners and decision-makers seeking to foster sustainable practices within the electronics industry.